Synthesis and Characterization of Two New Quinoxaline Derivatives (Journal of Academic Research, 2019)
Two new quinoxaline derivatives, 2-benzamide-3-3-cyanoquinoxaline-4-oxide (I) and N-(3-cyano-1,4-dioxy-quinoxaline-2-yl)-4-nitro-benzamide (II) were synthesized from 2-amino-3-cyano-quinoxaline-1,4-dioxide. The chemical structures of the two compounds were confirmed by IR, 1H and 13C NMR and MS spectroscopic analysis. The p-nitrobenzamide group is inserted in position 2 in quinoxaline-1,4-dioxide using benzoyl chloride as a reagent  under basic conditions. The structure of both compounds were confirmed by MS spectrometry, [C16H10N4O2]+ and [C16H10N5O5]+. The quasimolecular ions [M+H]+ of compounds were found equals to m/z 290.2 and 351.3, respectively